Analisis Pengaruh Inflasi Tingkat Bunga Nilai Tukar Dan Tingkat Bagi Hasil Terhadap Jumlah Penghimpunan Deposito Pihak Ketiga (Deposito Mudharabah 1 Bulan) (Studi Pada Bank Syariah Mandiri Periode 2011-2015) - Maisaroh, Annisa Nur, Drs. Wahyono.,MA,Ak (2017)
The purpose of this study was to analyze the effect of inflation, the deposit interest rate, Exchange Rate and the amount of profit sharing mudaraba deposits to total deposits at Bank SyariahMandiri (BSM). The data used in this study are monthly data from January 2011 to December 2015 taken from various sources. This study uses multiple linear regression analysis using the computer program SPSS version 20.0 and Microsoft Excel 2007. The results of the analysis indicated that partially of inflation, the deposit interest rate, the amount of profit sharing mudaraba deposits are not significant and, Exchange Rate significant to total of mudaraba deposits. Simultaneously variables total of inflation, the deposit interest rate, Exchange Rate and the amount of profit sharing mudaraba deposits are significant to total of mudharabah deposits. This is proved by value of sig-F 0.000 which is smaller than 5% of significance. Predictive ability of the four variables of the financing is 83,7%, as indicated by the amount of the adjusted R-square, while the remaining amount of 16,3% influenced by other factors that are not included in the study variables.